The association between mental health well-being and risky behaviors among adolescents in Argentina: Data from the 2018 global school health survey - Syed Muhammad Saad Jalil (22254274) (2025)
Purpose Mental health well-being is extremely important among adolescents due to this vulnerable period as well as its association with risky behaviors. The specific link between mental health well-being and risky behaviors has not been fully studied in Argentina. This study aims to find an association between poor mental health well-being and risky behaviors among adolescents in Argentina. Methods We analyzed cross-sectional data from the 2018 Global School Health Survey for Argentina which consisted of 56,981 adolescents. These adolescents participated in a self-reported questionnaire on aspects of their mental health well-being, including feelings of loneliness, feelings of worrisome, and suicidal ideation. Associations between mental health well-being and risky behaviors were examined using logistic regression analyses. Results Poor mental health well-being was associated with an increase in odds of engaging in risky behaviors. Adolescents who felt lonely had significant higher odds of consuming cigarettes (1.11), alcohol (1.08), and marijuana (1.21). Adolescents who felt so worried that they couldn’t sleep had higher odds of consuming cigarettes (1.17), alcohol (1.21), and marijuana (1.23). However, both variables showed no effect on unprotected sexual intercourse. Adolescents who considered attempting suicide had significant higher odds of consuming cigarettes (1.75), alcohol (1.39), and marijuana (1.602) as well as engaging in unprotected sexual intercourse (1.38). Discussion Our results show that poor mental health well-being is associated with an increase in risky behaviors. Moreover, our study shows negative parental influence, youth violence, increasing age, gender, and peer pressure as risk factors for adolescents to engage in harmful behaviors. Other Information Published in: Children and Youth Services Review License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.childyouth.2025.108555